2002
DOI: 10.1067/mge.2002.128106
|View full text |Cite
|
Sign up to set email alerts
|

Utility of EUS in the evaluation of cystic pancreatic lesions

Abstract: EUS alone is sensitive and accurate in identifying malignant/potentially malignant pancreatic cystic lesions. EUS-FNA to obtain specimens for cytopathologic analysis and determination of carcinoembryonic antigen levels, although safe, does not enhance diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
4
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 0 publications
6
99
4
4
Order By: Relevance
“…For larger tumors, even with an excellent positive predictive value, the negative predictive value was lower than 55%. Furthermore, the negative predictive value and diagnostic accuracy of EUS-FNA for cystic lesions were higher than 90%, which are consistent with other studies [29,30] . EUS-FNA has the following advantages over CT-or US-guided FNA: the shorter distance between the gut wall and tumor, the real time visualization of the needle, and the Doppler scanning to avoid punctures of the adjacent blood vessels [10,11] .…”
Section: Discussionsupporting
confidence: 92%
“…For larger tumors, even with an excellent positive predictive value, the negative predictive value was lower than 55%. Furthermore, the negative predictive value and diagnostic accuracy of EUS-FNA for cystic lesions were higher than 90%, which are consistent with other studies [29,30] . EUS-FNA has the following advantages over CT-or US-guided FNA: the shorter distance between the gut wall and tumor, the real time visualization of the needle, and the Doppler scanning to avoid punctures of the adjacent blood vessels [10,11] .…”
Section: Discussionsupporting
confidence: 92%
“…Sedlack et al in a retrospective study of 111 patients at Mayo Clinic found that cytology had 100% specificity and 27% sensitivity for mucinous cysts. This translates into 55% diagnostic accuracy [40]. Similar results were confirmed by Attasaranya et al from Indiana University in a retrospective study of 48 patients with pancreatic cysts.…”
Section: Cytological Evaluationsupporting
confidence: 71%
“…Main duct IPMN appears as a cystic dilation of the main pancreatic duct and it could be either segmental or diffuse in nature. EUS can also identify features that are worrisome for malignancy such as solid component, thick septae or lymphadenopathy [40,41]. However, EUS alone cannot differentiate benign from malignant cysts [42].…”
Section: Cyst Morphologymentioning
confidence: 99%
“…EUS can be considered complementary for distinguishing such lesions. 19,20 US-FNA sampling of cystic fluid distinguishes mucinous from non-mucinous cysts with high specificity by measurement of cyst fluid CEA levels but does not predict malignancy. 21 However, when ERCP does not visualize a part of the pancreatic duct or common bile duct, this area is usually seen well on EUS.…”
Section: Interventional Eus Proceduresmentioning
confidence: 99%